Circular RNA USP1 regulates the permeability of blood‐tumour barrier via miR‐194‐5p/FLI1 axis. Issue 1 (26th October 2019) - Gao, Yang; Wu, Peiqi; Ma, Yawen; Xue, Yixue; Liu, Yunhui; Zheng, Jian; Liu, Xiaobai; He, Qianru; Ma, Jun; Liu, Libo; Wang, Ping
Abstract: Recent studies indicate circular RNAs are related to dysregulation of vascular endothelial cell function, yet the underlying mechanisms have remained elusive. Here, we characterized the functional role of circular RNA USP1 (circ‐USP1) in the regulation of the blood‐tumour barrier (BTB) permeability and the potential mechanisms. In the current study, the circ‐USP1 expressing level was up‐regulated in glioma cerebral microvascular endothelial cells (GECs) of the BTB model in vitro. Knockdown of circ‐USP1 disrupted the barrier integrity, increased its permeability as well as reduced tight junction‐related protein claudin‐5, occludin and ZO‐1 expressions in GECs. Bioinformatic prediction and luciferase assay indicated that circ‐USP1 bound to miR‐194‐5p and suppressed its activity. MiR‐194‐5p contributed to circ‐USP1 knockdown‐induced increase of BTB permeability via targeting and down‐regulating transcription factor FLI1. Furthermore, FLI1 regulated the expressions of claudin‐5, occludin and ZO‐1 in GECs through binding to their promoter regions. Single or combined treatment of circ‐USP1 and miR‐194‐5p effectively promoted anti‐tumour drug doxorubicin across BTB to induce apoptosis of glioma cells. Overall, this present study identified the crucial regulation of circ‐USP1 on BTB permeability via miR‐194‐5p/FLI1 axis‐mediated regulation of tight junction proteins, which might facilitate the development of therapeutics against human gliomas.